A Critical Exploration to Godfrey Higgins's Apology from the Prophet Muhammad (SAW) - Hüseyin Çaksen (MAQOLAT: Journal of Islamic Studies, 2024)
In the book, “An Apology for the Life and Character of the Celebrated Prophet of Arabia, Called Mohamed, or The Illustrious,” Godfrey Higgins (1772-1833) presents “Persian empire and the oriental part of the Roman empire at the beginning of the seventh century,” “the emergence of Islam,” “the Prophet Muhammad’s (Sallallahu Alayhi Wa Sallam [SAW]) character, and mission,” “there is no god but Allah,” and “Muhammad (SAW) is the messenger of Allah.” He also compared Christianity (Bible) and Islam (Qur'an) in detailed. Higgins noted that the object of the book is to abate the spirit of intolerance that existed between Christians and Muslims. The review emphasizes the book's contribution to fostering a rational understanding of the Prophet Muhammad (SAW) and Islam for researchers interested in Islamic history and those who are curious about the Prophet Muhammad (SAW) and Islam.